EFFECTIVE MONITORING, TREATMENT AND PREVENTION OF ANEMIA CONCURRENT WITH HEART FAILURE IN THE CONDITIONS OF THE FERGANA VALLEY (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
This article provides a comprehensive analysis of the pathogenetic mechanisms, epidemiological burden, diagnostic approaches, and evidence-based treatment strategies for anemia coexisting with heart failure, with special emphasis on the clinical context of the Fergana Valley region. The cardiorenal anemia syndrome, hepcidin-mediated iron sequestration, erythropoietin resistance, and chronic neurohormonal activation are identified as the principal pathogenetic drivers worsening both conditions synergistically.